PERSEPSI AUDITOR INTERNAL DAN AUDITEE TERHADAP EXPECTATION GAP TERKAIT DENGAN INDEPENDENSI, KOMPETENSI PROFESIONAL DAN PENGAWASAN PADA INSPEKTORAT KOTA BALIKPAPAN - , Yanzil Azizil Y; , Taufikur Rahman, SE., MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to examine empirically whether there are differences in the perception of the internal auditor and the auditee aboutt expectation gap related to the independence of the internal auditor, internal auditor professional competence, and supervision of the process undertaken internal auditors. The method is used in this study namely survey method. This study uses census techniques for internal auditors and porpusive sampling techniques for the auditee. Sample in this study are the internal auditor and the auditee of Inspectorate Balikpapan City located within the Government City of Balikpapan. The methods of data collection use questionnaires with Likert scale. The validity test of using Perarson Product Moment Correlation and Reliability tests using Cronbach's Alpha technique and test normality using Kolmogorov-Smirnov One Sample Test. Then analyzed using the Mann-Whitney test, which is one non-parametric test using SPSS version 20 for windows. Based on the results of the hypothesis testing that there is an expectation gap between the internal auditor and the auditee related to independence, professional competence, and supervision of the Inspectorate of Balikpapan.